THE RELEVANCE OF AN INTEGRATIVE APPROACH IN TRAINING UNIVERSITY STUDENTS IN RADIATION MEDICINE AND TECHNOLOGY (Conferencea, 2024)
With the development of technology and technology, the newest modern disciplines are developing at a very fast pace, the need for which is growing day by day. These are: robotics, mechatronics, alternative energy sources, modern logistics, cluster production and industry, etc.